Anthracyclines-contra cruciform extrusion in DNA regulating sequences - Viglasky, Viktor (Endocrine, metabolic & immune disorders drug targets, 2006)
Despite the existence of a wealth of structural and theoretical data relating to palindromic sequences in the genome, the mechanism of cruciform formation in the presence of anthracyclines in miscellaneous biological processes is still poorly understood. Generally, DNA intercalators influence the DNA superhelicity, which plays a key role in the cruciform formation in DNA molecules. The potential of DNA intercalating ligands on the stabilization/destabilization of cruciform in DNA is discussed. Here, the indirect impact of anthracyclines to cell developing and surviving is analyzed for the first time. Primarily, the anthracycline modifies the helical properties of DNA and the overall DNA structure, and secondarily alters any cruciform-dependent processes, mainly DNA replication and transcription.
Keywords: antracykliny; financování organizované; interkalátory; Animals; DNA, Superhelical; konformace nukleové kyseliny; Financing, Organized; Temperature; DNA; lidé; superhelikální DNA; zvířata; Intercalating Agents; Anthracyclines; teplota; Nucleic Acid Conformation; Humans